Murottal Quran Therapy Intervention to Reduce Anxiety Level of Asthma Client - Suhanda; Rapiyudin; Masluh Aziz, Iman; Nurapandi, Adi; Firmansyah, Andan; Setiawan, Henri (Yayasan Inspirasi El Burhani, 2022)
Objective: The objective of this study was to intervene to reduce anxiety in Asthma clients so that excessive anxiety does not occur by listening to the Murottal Al Quran. Method: The study was conducted using a case study design with an evidence-based practice implementation approach that focuses on nursing interventions. The research was conducted at the BLUD of Banjar City General Hospital on 27-31 May 2022. The participants in this study were NY clients. S, 65 years old, female, complains of shortness of breath and anxiety. The process of assessing and establishing a diagnosis is focused on the main problem. Objective and subjective data become a reference for periodic evaluation of nursing implementation. Result: The client gave an acknowledgment of non-existent anxiety after being given a murotal al-quran intervention. Conclusion: The Murotal Al-Quran intervention is supposed to be effective in reducing anxiety in asthmatic clients as evidenced by the client's subjective acknowledgment even though it has not been supported by normal breathing frequency as an indicator of physical health. Theoretically, this research does not conflict with previous research so that it can be a reference in future research. Clinically, the Al-Quran murotal intervention can be one of the intervention treatments to reduce anxiety levels in clients with chronic diseases such as asthma in hospitals and health centers.